2011
DOI: 10.1167/iovs.11-8353
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Role of VEGF in the Adult Retinal Pigment Epithelium

Abstract: These results indicate that VEGF plays a critical role in survival and maintenance of RPE integrity. Potential undesired off-target effects should be considered with chronic use of anti-VEGF agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
126
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(132 citation statements)
references
References 39 publications
(53 reference statements)
5
126
0
1
Order By: Relevance
“…Failure in RPE differentiation results in attenuation of VEGF expression, which is the likely molecular mechanism for atrophy of the choriocapillaris. RPE cells express high amounts of VEGF during embryonic development and in adult life (Ford et al 2011), which are essential for both the formation and the maintenance of the choriocapillaris. Conditional VEGF deficiency in the developing RPE results in the absence of the choriocapillaris in mutant mice (Marneros et al 2005;Le et al 2010), and conditional deletion of VEGF in the adult mouse RPE rapidly leads to ablation of the choriocapillaris .…”
Section: Discussionmentioning
confidence: 99%
“…Failure in RPE differentiation results in attenuation of VEGF expression, which is the likely molecular mechanism for atrophy of the choriocapillaris. RPE cells express high amounts of VEGF during embryonic development and in adult life (Ford et al 2011), which are essential for both the formation and the maintenance of the choriocapillaris. Conditional VEGF deficiency in the developing RPE results in the absence of the choriocapillaris in mutant mice (Marneros et al 2005;Le et al 2010), and conditional deletion of VEGF in the adult mouse RPE rapidly leads to ablation of the choriocapillaris .…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that low levels of ROS VEGF and VEGF 165 b proteins. Although expression of VEGF proteins has been previously described in several in vitro retinal cells [29,30] the co-localization of VEGF and VEGF 165 b in D407 RPE cells was unknown. Previous studies have also shown that in culture RPE cells, VEGF 165 is one of the predominant isoforms expressed, from all the members of the VEGF family [29,30].…”
Section: Glucose Induce Ros Production In Rpe Cellsmentioning
confidence: 99%
“…Although expression of VEGF proteins has been previously described in several in vitro retinal cells [29,30] the co-localization of VEGF and VEGF 165 b in D407 RPE cells was unknown. Previous studies have also shown that in culture RPE cells, VEGF 165 is one of the predominant isoforms expressed, from all the members of the VEGF family [29,30]. RPE cells were exposed to different glucose concentrations to mimic a physiological (5.5 mM) and a diabetic (25 mM) condition and it was found that VEGF and VEGF 165 b were differently regulated by glucose.…”
Section: Glucose Induce Ros Production In Rpe Cellsmentioning
confidence: 99%
“…16 Moreover, the neutralization of VEGF in cultured RPE led to increased cell death, and VEGF neutralization in vivo resulted in damage to the RPE-choroid complex, including vacuolization, loss of association with photoreceptor outer segments, and decreased choriocapillaris fenestrations. 17 We acknowledge that the present study has a number of limitations, including the reduced number of patients, the short-term follow-up, and the subjective classification of the FAF patterns of the CNV. An additional shortcoming is the absence of a control group providing a more precise appraisal of the anti-VEGF effects.…”
Section: Discussionmentioning
confidence: 91%